The Rhetorical Impact of Polylingualism Employed by Lithuanian Politicians on Facebook - Gabrėnaitė, Eglė; Biržietienė, Skirmantė (Respectus Philologicus, 2022)
The aim of the research presented in this article aims to determine the impact of polylingualism on the effectiveness of political rhetoric in Lithuania. The study focuses on elements borrowed from other languages and used by Lithuanian politicians in their Facebook posts. In addition, the motivation behind such use is explored, aiming to establish whether polylingualism is part of a conscious effort of political communication in order to build a positive image. Within the scope of this research are Facebook posts containing cases of polylingualism, specifically, English-language inserts. The authors of these posts are prominent politicians who are native Lithuanian speakers engaged in active communication on social media. Collected during the period of 2018–2021, the research material was examined using the method of rhetorical discourse analysis, resulting in the identification of characteristic instruments of persuasion, i.e. the tools which help enhance the effectiveness of certain discourse. The researchers aimed to determine the general patterns and dominant tendencies of mixed speech within the political discourse on social media. The research reveals the use of polylingualism as a stylistic tool imitating informal speaking and creating contextual discourse.
Keywords: mixed speech; polylingualism; English inserts; rhetoric; political discourse; Lithuanian